2022
DOI: 10.1002/jcu.23359
|View full text |Cite
|
Sign up to set email alerts
|

Shear‐wave elastography evaluation of thenar muscle in carpal tunnel syndrome

Abstract: Purpose We aim to evaluate the shear wave velocity (SWV) of the thenar muscle as an adjunct diagnostic tool for carpal tunnel syndrome (CTS). Methods Ninety‐two wrists with CTS and 30 control wrists without CTS underwent ultrasonographic evaluation of thenar muscle and median nerve including shear‐wave elastography. Cross sectional area (CSA) of medial nerve and SWV of thenar muscle and median nerve were evaluated. CTS patients were assessed for Boston CTS, Padua CTS, modified Hirani grading scores, and nerve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Unlike conventional MRI and ultrasound evaluations of muscle size and echogenicity, SWE is characterized by its ability to easily evaluate muscle mechanical properties and thus may have the potential to estimate muscle dysfunction with higher precision than conventional imaging modalities. A recent study of SWE of the thenar muscle in CTS showed that the elastic modulus of the thenar muscle in patients’ CTS was increased compared with that of control subjects, and was significantly negatively correlated with EP parameters 7 . This study demonstrates the SWE has the potential to provide another simple and noninvasive assessment of the severity of CTS.…”
Section: Introductionmentioning
confidence: 56%
See 2 more Smart Citations
“…Unlike conventional MRI and ultrasound evaluations of muscle size and echogenicity, SWE is characterized by its ability to easily evaluate muscle mechanical properties and thus may have the potential to estimate muscle dysfunction with higher precision than conventional imaging modalities. A recent study of SWE of the thenar muscle in CTS showed that the elastic modulus of the thenar muscle in patients’ CTS was increased compared with that of control subjects, and was significantly negatively correlated with EP parameters 7 . This study demonstrates the SWE has the potential to provide another simple and noninvasive assessment of the severity of CTS.…”
Section: Introductionmentioning
confidence: 56%
“…A recent study of SWE of the thenar muscle in CTS showed that the elastic modulus of the thenar muscle in patients' CTS was increased compared with that of control subjects, and was significantly negatively correlated with EP parameters. 7 This study demonstrates the SWE has the potential to provide another simple and noninvasive assessment of the severity of CTS. However, the thenar muscles represent a complex grouping of small muscles in close proximity, with multiple heads, and with varying innervation, and the superficial and deep muscles are shown together on an ultrasound image, 8 so it is essential that SWE measurement be performed reproducibly and reliably on a specific muscle belly if the measurements are to be clinically useful.…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…• The Young's modulus may have diagnostic value in staging of CTS 35 Thenar musculature • SWV of the thenar musculature was significantly greater in patients with CTS than control patients 36 • SWV of the thenar musculature was inversely correlated with modified Hirani score 36 Median nerve (MN) • Young's modulus of the MN is significantly greater in patients with CTS 35 • Young's modulus of the MN was significantly greater in patients with moderate/severe CTS versus patients with mild CTS or without CTS 37 • A cutoff point of 57 kPa separated a diagnosis of moderate/severe CTS from mild CTS 37 • The combination of CSA at the level of the pronator quadratus with elastography measurement resulted in a specificity and sensitivity of 100% and 93% for CTS diagnosis 40 T A B L E 4 Utility of shear wave elastography (SWE) in the diagnosis of various lower extremity pathologies.…”
Section: Key Resultsmentioning
confidence: 99%
“…Carpal tunnel syndrome (CTS) Five studies were identified evaluating the use of SWE for diagnosis and grading of CTS. [35][36][37][38][39] Structures evaluated include the median nerve, transverse carpal…”
Section: Hand/wristmentioning
confidence: 99%